Moringa Oleifera Addition to Puding on Organoleptic Test and Nutritional Content - Renita Afriza; Defniwita Yuska; Elsyie Yuniarti (Sarana Ilmu Indonesia (salnesia), 2023)
Efforts are being made to address malnutrition in Indonesia, one of which is food diversification based on innovation and the development of additional food formulations to increase toddler immunity. One of the progs being developed is moringa oleifera. Moringa leaves contain a variety of nutrients, including protein, ß-carotene, vitamin C, iron, zinc, and calcium. Combining jelly with vegetables is one way to help parents deal with their children who don't like vegetables. This study looked at how adding moringa leaf flour to pudding affected the amount of calcium, iron, and zinc, as well as organoleptic testing. This type of study is an actual experiment with four (four) treatments of adding moringa leaf powder and a fully randomized design, namely 0 g, 3 g, 5 g and 7 g. Data analysis utilizing the Mann Whitney and Kruskal-Wallis tests. 25 moderately trained panelists underwent organoleptic testing, and the amounts of Ca, Fe, and Zn were measured at the Baristand Padang. According to the study's findings, pudding with 3g of moringa leaf flour added was the best treatment when combined with Ca 116,53 mg, Fe 2,05 mg, and Zn 5,17 mg. Therefore, it can be inferred that adding moringa leaf flour to pudding has an impact on the organoleptic tests, Ca, Fe, and Zinc levels.